Melanoma in situ mimicking a Lichen planus-like keratosis - Sisti, Andrea; Fallaha, Amgiad; Tassinari, Juri; Nisi, Giuseppe; Grimaldi, Luca; Eisendle, Klaus (Acta Biomedica Atenei Parmensis, 2018)
The incidence of melanoma has steadily increased over the past three decades. Melanoma in situ (MIS),  defined as melanoma that is limited to the epidermis, contributes to a disproportionately high percentage of this rising incidence. Amelanotic melanoma presents as an erythematous macule or plaque and may initially be misdiagnosed as an inflammatory disorder. We report a case of amelonatic MIS raised on non-sun-exposed skin, inducing a lichen planus-like keratosis as inflammatory reaction, which clinically masked the melanoma.